2018
DOI: 10.1063/1.5050426
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics modeling of the Hugoniot states of aluminum

Abstract: In this study, molecular dynamics (MD) simulations coupled with multi-scale shock technique (MSST) are used to predict the Hugoniot curve PH, Grüneisen coefficient γ and melting temperature Tm of single crystal (SC) and nanocrystalline (NC) aluminum (Al) with grain sizes of 6 and 60 nm at dynamic high pressure. The linear relation between the shock wave velocity and particle velocity is reproduced, and the results indicate that there is nearly no difference for the Hugoniot of SC and NC Al, which could be expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…A detailed comparison of MD simulation results and experimental data is presented in Table 2. From Table 2, it can be observed that the volume sound speed C 0 in SC iron is higher than that in NC iron; however, the fitting parameter λ in SC iron is lower than that in NC iron, and the same characteristics are also observed in SC and NC Al [5]. The maximum relative error of C 0 between the experiment and SC iron is 3.34%, and the maximum relative error of NC iron is 1.89%.…”
Section: Shock Hugoniot Pressure and Internal Energymentioning
confidence: 68%
See 4 more Smart Citations
“…A detailed comparison of MD simulation results and experimental data is presented in Table 2. From Table 2, it can be observed that the volume sound speed C 0 in SC iron is higher than that in NC iron; however, the fitting parameter λ in SC iron is lower than that in NC iron, and the same characteristics are also observed in SC and NC Al [5]. The maximum relative error of C 0 between the experiment and SC iron is 3.34%, and the maximum relative error of NC iron is 1.89%.…”
Section: Shock Hugoniot Pressure and Internal Energymentioning
confidence: 68%
“…where Q, q, A, and B are material constants; δ = V 0K /V; and ρ 0K is the material density at 0. At P = 0 and T = 0, we can assume that the first-order and second-order derivatives of P H , isentropic P s , and P c are almost equal [5,46]. Thus, we have:…”
Section: Cold Pressure (P C ) and Cold Energy (E C )mentioning
confidence: 99%
See 3 more Smart Citations